Maternal Perception, Hesitancy, and Satisfaction Toward Childhood Immunization in Primary Health Centers, Hafr Al-Batin: A Multicenter Cross-Sectional Study from Eastern Saudi Arabia - Thirunavukkarasu A; Falji A Alanazi M; Al-Hazmi AH; Farhan ALruwaili B; Awad Alsaidan A; Alshami M Alruwaili T; Abdulaziz M Algaed M; Kaseb Alsharari A; Alenazi RH; Alshalan AM; Alshalan SM (Dove Medical Press, 2023)
Ashokkumar Thirunavukkarasu,1 Mohammed Falji A Alanazi,2 Ahmad Homoud Al-Hazmi,1 Bashayer Farhan ALruwaili,1 Aseel Awad Alsaidan,1 Thamer Alshami M Alruwaili,3 Majed Abdulaziz M Algaed,4 Areej Kaseb Alsharari,4 Ragad Humaidi Alenazi,4 Amal Muteb Alshalan,5 Sultan Muteb Alshalan6 1Department of Family and Community Medicine, College of Medicine, Jouf University, Sakaka, Saudi Arabia; 2Department of Public Health, Hafr Al Batin Health Affairs, Hafr Al Batin, Saudi Arabia; 3Department of Pediatrics, College of Medicine, Jouf University, Sakaka, Saudi Arabia; 4College of Medicine, Jouf University, Sakaka, Saudi Arabia; 5Department of Medicine, King Abdulaziz Specialist Hospital, Sakaka, Saudi Arabia; 6Medical Department, North Medical Tower hospital, Arar, Saudi ArabiaCorrespondence: Ashokkumar Thirunavukkarasu, Department of Family and Community Medicine, College of Medicine, Jouf University, Sakaka, 72388, Saudi Arabia, Tel +966-599739619, Email ashokkumar@ju.edu.saBackground: Consumer perception of and satisfaction with vaccination services is a critical and commonly used indicator for evaluating the quality of services provided by concerned authorities. The present survey assessed maternal perceptions, hesitancy, satisfaction, and factors associated with childhood immunization services provided at the primary health centers (PHCs) of eastern Saudi Arabia.Methods: The current analytical cross-sectional study included mothers of childhood vaccine beneficiaries attending PHCs in Hafr Al-Batin. We collected data related to mothers' perceptions, hesitancy, and satisfaction using a validated Arabic version of the data collection tool. Factors associated with low and high satisfaction with the immunization services were evaluated using logistic regression analysis. We performed Spearman correlation test to identify the correlation between the perception and satisfaction scores.Results: Of the 675 participants, 87.4% were satisfied with the immunization services provided at the PHCs. The participants' satisfaction was significantly associated with the immunized child's age group (adjusted odds ratio [AOR] = 1.89, 95% CI = 1.39- 2.89, p = 0.037) and occupation status (AOR = 1.42, 95% CI = 1.17- 1.74, p = 0.024). Vaccine hesitancy was significantly associated with the mother's age group (AOR = 1.89, 95% CI of AR = 1.35- 3.39, P = 0.003) and number of children (AOR = 1.42, 95% CI of AR = 1.17- 1.74, P = 0.024), Additionally, we found a significant positive correlation (Spearman's rho = 0.207, p < 0.001) between perception and satisfaction scores.Conclusion: We recommend targeted health education programs for mothers to improve their perceptions and the importance of all recommended childhood vaccines. Additionally, we suggest continuing maternal satisfaction assessments to enhance and maintain the quality of vaccination services.Keywords: childhood vaccines, adverse effect, satisfaction, hesitancy, perception, Saudi Arabia